Dynamic modulation of the non-canonical NF-κB signaling pathway for HIV shock and kill - Chandrasekar, Aswath P.; Maynes, Mark; Badley, Andrew D. (Frontiers in Cellular and Infection Microbiology, 2024)
HIV cure still remains an elusive target. The “Shock and Kill” strategy which aims to reactivate HIV from latently infected cells and subsequently kill them through virally induced apoptosis or immune mediated clearance, is the subject of widespread investigation. NF-κB is a ubiquitous transcription factor which serves as a point of confluence for a number of intracellular signaling pathways and is also a crucial regulator of HIV transcription. Due to its relatively lower side effect profile and proven role in HIV transcription, the non-canonical NF-κB pathway has emerged as an attractive target for HIV reactivation, as a first step towards eradication. A comprehensive review examining this pathway in the setting of HIV and its potential utility to cure efforts is currently lacking. This review aims to summarize non-canonical NF-κB signaling and the importance of this pathway in HIV shock-and-kill efforts.